2016
DOI: 10.5173/ceju.2016.805
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic calyceal diverticulectomy

Abstract: Calyceal diverticulum are cystic cavities within renal parenchyma lined by nonsecretory epithelium and communicating with the collecting system via a narrow channel. Usually they are asymptomatic and under one centimeter. The indications of surgical treatment are usually the symptomatic ones (hematuria, pain, infection), in most cases associated with the calculi. The development of minimally invasive approaches like laparoscopy is by displaying traditionally invasive approaches. We described a laparoscopic tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recurrent urinary tract infection, severe hematuria) Not mentioned in the literature 7 China Peng YH, et al [ 8 ] 2011 60 Male Combined retrograde urography + CT + MRI urography Diverticulum of renal calyces combined with left hydronephrosis and bilateral renal cysts Low Back Pain left kidney:101*81 73*61 right kidney:61*48 22*19 None Patients receive non-surgical treatment At 2 years of follow-up, the patient had no worsening of ipsilateral abdominal pain and no enlargement of the renal calyx diverticulum. 8 Spain Bonastre C, et al [ 9 ] 2016 24 Female Ultrasound of the abdomen+ CT Calvarial diverticulum Left back pain and fever None None Laparoscopic nephrological diverticulectomy Jackson-Pratt drainage tube was placed. CT on the third day showed that the diverticulum had subsided with no signs of recurrence.…”
Section: Case Presentationmentioning
confidence: 99%
“…Recurrent urinary tract infection, severe hematuria) Not mentioned in the literature 7 China Peng YH, et al [ 8 ] 2011 60 Male Combined retrograde urography + CT + MRI urography Diverticulum of renal calyces combined with left hydronephrosis and bilateral renal cysts Low Back Pain left kidney:101*81 73*61 right kidney:61*48 22*19 None Patients receive non-surgical treatment At 2 years of follow-up, the patient had no worsening of ipsilateral abdominal pain and no enlargement of the renal calyx diverticulum. 8 Spain Bonastre C, et al [ 9 ] 2016 24 Female Ultrasound of the abdomen+ CT Calvarial diverticulum Left back pain and fever None None Laparoscopic nephrological diverticulectomy Jackson-Pratt drainage tube was placed. CT on the third day showed that the diverticulum had subsided with no signs of recurrence.…”
Section: Case Presentationmentioning
confidence: 99%